Physiological responses obtained during exercise on the StairMaster Gauntlet with and without the use of hands - Heilman, Paula S. (My University, 1991)
This investigation was designed to determine if there were sig diffs in the physiological responses (VO,, VE, METS, RER, Kcals, HR, and RPE) with hands (WH) or without hands (WOH) during exercise on the StairMaster Gauntlet (SM). Two discontinuous protocols utilizing 6, 8, 11, 14, and 17 METS were performed on 20 healthy college females. The ANOVA indicated there were sig (p c .05) diffs between all stages and methods WOH condition which resulted in higher values. Since the ANOVA indicated a sig (p c .05) interaction, the Bonferroni method indicated that all values representing V02, VE, METS, Kcals, and HR were sig (p c . 01) higher WOH. The RER at 11 and 14 METS were sig (p C .Ol) lower WH. The RPE at 8, 11, and 14 METS were also sig (p c .01) lower WH. As the intensity increased, the differences in methods also increased for all physiological variables except HR. WH was found to overestimate the values at the higher intensities. It was concluded that the use of handrails during SM exercise decreases the metabolic requirements of exercise.
Keywords: Physical fitness for women - Testing; Step aerobics - Physiological aspects; StairMaster Gauntlet (Exercise machine)